Methods of Mechanical Mining of Compact-Rock—A Comparison of Efficiency and Energy Consumption - Kotwica Krzysztof; Małkowski Piotr (Energies, 2019)
This paper compares the methods of mechanical mining of rock in terms of their efficiency, energy consumption, and the durability of the tools they involve. It presents the advantages of mechanical heading-driving methods. In the first part, we described the methods used to assess rock workability, and the influence of rock types and parameters on mining efficiency. Furthermore, we discussed the compact-rock mining process in terms of the energy it consumes. We provided the description of the most common mechanical methods, such as milling, static crumpling and undercutting, including the tools involved, and the requirements and limitations for the use of these methods. The paper presents unique machinery solutions designed to reduce the energy consumed by mining processes. In the final part of the paper, we propose a solution to select the mechanical method of rock mining as a function of rock type and parameters.